The Effect of Analog GnRH before Laparoscopic Cystectomy to Ovarian Reserve which was Measured with anti MÃ¼llerian Hormone at Bilateral Endometriosis Cyst - Kanadi Sumapraja (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To know the effect of preoperative GnRH-a treatment to preserve the ovary after laparoscopic excision of endometriomas by measuring antimÃ¼llerian hormonal before and after operation and analize the correlation with age and size of the endometrioma. Methods: Double blind randomized control trial, which is done to patients with bilateral endometriomas in Raden Saleh Clinic. Subject devided into groups GnRH-a and placebo. Patient was undergoing laparoscopic excision after four weeks of medication (GnRHa or placebo). AMH Serum levels was measured before preoperative medication and four weeks after operation. Result: There were eight bilateral endometriomas (25% patients requirement), 4 patient GnRH-a and four patients placebo, all with primary infertility. The average changes of AMH serum level before and after laparoscopy ovarian cystectomy in GnRH-a groups was 0.011 ng/ml and placebo groups was 1.502. The average changes of AMH serum level, in age strativication on both groups show the same result, GnRH-a 0.035 and placebo 1.681. In diameter cyst strativication, GnRH-a 0.011 and placebo 1.090. Conclusions: With the restrictiveness of the patient, this study find GnRH-a therapy initiated before laparoscopic cystectomy has better outcomes in ovarian reserve compared with placebo, and also the same result in age and size of cyst strativication analize. [Indones J Obstet Gynecol 2011; 35-1: 14-7] Keywords: laparoscopic cystectomy, GnRH-a, ovarian reserve